IMPLEMENTASI KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU DENGAN SISTEM ZONASI PADA SMP NEGERI DI KOTA PADANG - Meylan Siswara Handani; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
This study aimed to analyze the implementation of policies in the New Student Admissions (PPDB) using the zoning system at State Junior High Schools in Padang City. This was a qualitative research using descriptive methods. Informants in this study were selected based on certain criteria using a purposive sampling technique. Data collection techniques used in this study were interviews and documentation. The data in this study were analyzed with interactive analysis model. Based on the results of this study and discussion, the implementation of policies in PPDB using the zoning system at State Junior High Schools in Padang City could be said to be quite good. However, there were several inhibiting factors, namely, the emergence of interpretation among the community, the lack of support and misunderstanding of the community; The tiered socialization system implemented by the Education Office was not maximal; and the time for the issuance of the technical instructions which was close to the time of PPDB implementation so that the socialization is not optimal.